Interfaith Marriage in Indonesia: a Critique of Court Verdicts - M. Ya'kub Aiyub Kadir; Fachrian Rzki (Yuridika, 2023)
This paper investigates the deviation of court decisions legalising interfaith marriage, as against Article 1 and Article 2 Paragraph (1) of Act Number 1 of 1974 concerning Marriage. Such a notion is discussed by the norms of six major religions in Indonesia. This paper utilises the doctrinal approach by analysing norms and their interpretation in practice. Doing so reconfirms the validity of marriage based on the One and Only God in which its performance ought to follow the rule of the respective religion and faith, which invalidates marriages between people of different religions. Interfaith marriage may be considered legal by one religion but unlawful by another. It simply means that the conformity between religious laws will render the status of legality of interfaith marriage. This paper found there is possibility that interfaith marriage may considered legal. Nevertheless, the judge and all concerned parties need to be aware of the laws of the respective religions and beliefs if one prohibits interfaith marriage. Even if the other permits it, the marriage will be considered unlawful by the prohibiting religion.